The politics behind scientific knowledge: Sustainable forest management in Latin America - Soler, Rosina; Lorenzo, Cristian; Gonzalez, Joel; Carboni, Lucas; Delgado, Juan; Diaz, Mayra; Manriquez, Monica D. R. Toro; Alejandro, Huertas Herrera (My University, 2021)
Sustainable Forest Management (SFM) seeks to achieve an equilibrium in the economic, social and environmental value of all types of forests. This practice contrasts with the conventional view of managing forests, in which the focus is productivity. Thus, discussions about conventional forest management versus sustainable forest management play a central role in the political and scientific agendas. However, knowledge production and its direction can be biased by different contextual factors such as the way funding is assigned by each country, institutional priorities, and constraints on international cooperation. With this paper, we aim to analyze the contribution of scientific knowledge produced in Latin America within the sustainable forest management research landscape by applying a literature review method (Scopus database for 2015-2018 period). Our results show a similar contribution of national and foreign funds and institutions supporting scientific knowledge about SFM in Latin America. Foreign funding comes mainly from United States of America, and Europe. Latin American authors lead high proportion of scientific articles, and authorship gender was more equitable between male and female researchers. The studies were mostly focused on conservation combined with productivity goals, as well as pure conservation goals, although social studies and restoration goals were also present. Our findings highlight a significant contribution to the paradigm shift in half of the scientific articles. Some studies provided recommendations (specific or general) derived from their results, but we did not detected a clear relationship with funding origin. Moreover, we found that the high contribution to the paradigm shift (studies supporting SFM instead of traditional management) came from institutions based in Latin America. This article aims to contribute to discussions related to scientific funding in Latin America, the North-South scientific relations, and the future of forest in times of climate change.
Keywords: forestry policies; international cooperation; literature review; natural resources; research and development; research funding